Acute post-traumatic locked knee - an unmasking of a rare knee disorder - Mohd Nizlan, Nasir; Abd Ghani, Fauzah; Tasarib, Rohaman (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Locked knees are commonly caused by meniscal tears, floating osteochondral bodies, ruptured anterior cruciate ligament (ACL) stump, or other mechanical origins in the knee. Some locked knees occur spontaneously, while in most cases, by a preceding knee trauma. Locked knees are rarely caused by a pathological growth in the knee. More unusually is the occurrence of locked knee caused by a pre-existing pathological entity after a traumatic event. We report a rare case of locking in the knee by a pre-existing knee condition presented only after trauma to the knee. This case emphasizes that locking in the knee can be caused by a pathology that may be asymptomatic until it is revealed by a traumatic event.